Relative hydrogen index as a fast method for the simultaneous determination of physicochemical properties of petroleum fractions. (15th December 2017) - Barbosa, Lúcio L.; Montes, Luciana F.; Kock, Flávio V.C.; Morgan, Vinícius G.; Souza, Andre; Song, Yi-Qiao; Castro, Eustáquio R.V.
Abstract: This work presents the use of the Relative Hydrogen Index (RHI) parameter obtained from the single–pulse Nuclear Magnetic Resonance (NMR) Free Induction Decay (FID) experiment as an efficient, fast and unique procedure for the determination of important physical and chemical properties of petroleum fractions. Four Brazilian crude oils were distillated according to ASTM D2892 to obtain a total of 42 fractions. RHI was determined using a Low Field – NMR (LF–NMR) spectrometer that operates at 2.2 MHz for the 1 H nucleus. The results showed strong correlations between RHI and the physicochemical properties: kinematic viscosity, API gravity, molecular weight, refractive index and translational self–diffusion coefficient. The paper demonstrates that the RHI parameter can be used as an alternative methodology in academy and industry to predict simultaneously those physicochemical properties of petroleum fractions, based solely on the results obtained by the single-pulse FID NMR technique.